Coupled influence of tectonics, climate, and surface processes on landscape evolution in southwestern North America - Alireza Bahadori; William E. Holt; Ran Feng; Jacqueline Austermann; Katharine M. Loughney; Tristan Salles; Louis Moresi; Romain Beucher; Neng Lu; Lucy M. Flesch; Christopher M. Calvelage; E. Troy Rasbury; et al. (Nature Communications, 2022)
Cenozoic landscape evolution of southwestern North America remains debated. Here, the authors reconstruct landscape using 4-D numerical models, which can explain extensional collapse and superficial geological record for the Basin and Range Province